ANTAGONISTIC POTENTIAL OF DIFFERENT TRICHODERMA SPP. AGAINST SCLEROTIUM ROLFSII AND FUSARIUM OXYSPORUM F. SPP. LYCOPERSICI (Journal of Plant Disease Sciences, 2025)
Tomato (Solanum lycopersicum L.) is one of the most widely cultivated vegetable crops worldwide and is valued for its nutritional and economic importance. Often referred to as the “poor man’s orange” due to its high vitamin C content, tomato cultivation has expanded considerably; however, its production is severely constrained by soil-borne pathogens such as Fusarium, Rhizoctonia and Sclerotium species.Soil samples were collected from different tomato-growing regions of Parbhani district, Maharashtra, and six native Trichoderma isolates were obtained from the tomato rhizosphere. Based on morpho-cultural characteristics, the isolates were identified as Trichoderma harzianum, Trichoderma asperellum, Trichoderma virens, Trichoderma koningii, Trichoderma longibrachiatum and Trichoderma hamatum. These isolates were evaluated under in vitro conditions against Sclerotium rolfsii and Fusarium oxysporum f. sp. lycopersici using the dual culture technique. Among the tested isolates, Trichoderma harzianum (T₁) proved to be the most effective against Sclerotium rolfsii, recording the lowest mycelial growth of 15.50, 18.33 and 27.65 mm on the third, fifth and seventh days, respectively, followed by Trichoderma asperellum (T₂), which showed 16.03, 19.04 and 28.17 mm colony diameter. Against Fusarium oxysporum f. sp. lycopersici, Trichoderma harzianum (T₁) again exhibited the highest antagonistic activity, recording minimum mycelial growth of 30.12, 23.96 and 30.12 mm on the third, fifth and seventh days, respectively, with maximum inhibition of 52.09, 61.06 and 66.53 per cent. The study demonstrates the strong biocontrol potential of native Trichoderma species, particularly Trichoderma harzianum, against major soil-borne pathogens of tomato, indicating their suitability for eco-friendly disease management strategies.
Keywords: Fusarium, In vitro, Sclerotium, Tomato, Trichoderma